2014
DOI: 10.1016/j.watres.2013.09.052
|View full text |Cite
|
Sign up to set email alerts
|

Improved virus removal by high-basicity polyaluminum coagulants compared to commercially available aluminum-based coagulants

Abstract: We investigated the effects of basicity, sulfate content, and aluminum hydrolyte species on the ability of polyaluminum chloride (PACl) coagulants to remove F-specific RNA bacteriophages from river water at a pH range of 6-8. An increase in PACl basicity from 1.5 to 2.1 and the absence of sulfate led to a reduction of the amount of monomeric aluminum species (i.e., an increase of the total amount of polymeric aluminum and colloidal aluminum species) in the PACl, to an increase in the colloid charge density of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 26 publications
2
19
1
Order By: Relevance
“…PAC G2.0 possesses the highest Al b content of 70.04% in the research, and the value is far larger than that in the similar research (Li Liu and Li, 2010). It has been reported that high Al b content resulted in the excellent coagulation performance in the water treatment (Shirasaki et al, 2014;Shu-xuan et al, 2014;Xu and Gao, 2012). The distributions of Al 13 and Al m in PAC G with different basicity values possess the similar tendency (Table 1 and Fig.…”
Section: Characterization Of Pac Gmentioning
confidence: 64%
See 4 more Smart Citations
“…PAC G2.0 possesses the highest Al b content of 70.04% in the research, and the value is far larger than that in the similar research (Li Liu and Li, 2010). It has been reported that high Al b content resulted in the excellent coagulation performance in the water treatment (Shirasaki et al, 2014;Shu-xuan et al, 2014;Xu and Gao, 2012). The distributions of Al 13 and Al m in PAC G with different basicity values possess the similar tendency (Table 1 and Fig.…”
Section: Characterization Of Pac Gmentioning
confidence: 64%
“…Aluminum species distribution is presented by calculating the contents of Al a , Al b and Al c , and it profoundly influences the coagulation efficiency of PAC (Shirasaki et al, 2014;Shu-xuan et al, 2014). The aluminum species in PAC G were measured via the application of Al-Ferron timed spectrophotometric method based on the different reaction time of hydroxyl-aluminum with the Ferron reagent (8-hydroxy-7-iodoquinoline-5-sulfonic acid) (Sinopharm Chemical Reagent Co., Ltd., China) (Feng et al, 2007).…”
Section: Ferron Assaymentioning
confidence: 99%
See 3 more Smart Citations